Optimalisasi Kinerja Karyawan melalui Strategi Pengembangan Karir: Studi Kasus pada Entitas Bisnis Lokal Wikowi Nged Singkep - I Komang Trisna Eka Putra; N. L. Ayu Wanti; Aditya Manggala, RS (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2026)
In the dynamic era of retail business competition, human resource (HR) management through career development has become a primary catalyst in improving organizational performance. However, local business entities often face obstacles in mapping structured career paths. This study aims to analyze the effectiveness of career development strategies and explore employee perspectives on their impact on performance at CV. Wikowi Nged Singkep, Denpasar. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews, observation, and documentation studies of five key informants selected via purposive sampling. Data analysis was conducted using the Miles and Huberman interactive model. The results showed a disparity in perception between management and operational staff. On the one hand, periodic performance evaluations, mentoring, and managerial flexibility especially in accommodating local socio-cultural activities proved effective in maintaining work motivation and loyalty. On the other hand, the absence of clear vertical career mobility routes triggered a sense of stagnation (career plateau) among lower-level operational staff. In conclusion, organically driven career development strategies have maintained productivity rhythms but require systematization. Management is advised to design a career matrix based on job rotation or job enlargement to ensure the sustainability of competitive HR performance.